Does income inequality affect environmental sustainability? Evidence from the ASEAN-5 - Masud, Muhammad Mehedi; Kari, Fatimah; Banna, Hasanul; Saifullah, Md Khaled (Taylor & Francis, 2018)
Income gap among the Association of Southeast Asian Nations (ASEAN) has widened, while environment degradation has worsened since the 1990s. Using the Gini coefficient as a measure of income inequality, this paper attempts to examine whether the increasing income gap would have adverse effects on environmental sustainability and the causality relationship between income inequality and environmental sustainability. Using data from the World Bank and the Standardized World Income Inequality Database, this paper deployed the Granger causality and panel regression tests to examine these relationships on the ASEAN members of Indonesia, Malaysia, the Philippines, Thailand and Vietnam over the period of 1985–2015. The empirical results indicate that bi-directional causality relationship between income inequality and environmental sustainability exists among the bottom 40%, but the causality relationship results for the overall sample are mixed. The evidence shows that policy-makers in these countries should reduce income inequality to strengthen environmental sustainability.